2013
DOI: 10.1155/2013/984041
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modifying Therapies for Alzheimer's Disease Targeting AβOligomers: Implications for Therapeutic Mechanisms

Abstract: Several lines of evidence indicate that amyloid β (Aβ), particularly Aβ oligomers (AβOs), plays a causative role in Alzheimer's disease. However, the mechanisms underlying the action of an anti-AβO antibody to clarify the toxic action of AβOs remain elusive. Here, we showed that the anti-AβO antibody (monoclonal 72D9) can modify the Aβ aggregation pathway. We also found that 72D9 directly sequesters both extracellular and intraneuronal AβOs in a nontoxic state. Thus, therapeutic intervention targeting AβOs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These antibodies reduce tau pathology, also seen earlier with the broader-based A11 oligomer antibody [132]. Another AβO antibody (72D9) sequestered both extracellular and intraneuronal AβOs [115]. Sequestering AβOs in older Tg mice attenuates synapse loss near plaques and abolishes loss further away [31].…”
Section: Therapeuticsmentioning
confidence: 96%
“…These antibodies reduce tau pathology, also seen earlier with the broader-based A11 oligomer antibody [132]. Another AβO antibody (72D9) sequestered both extracellular and intraneuronal AβOs [115]. Sequestering AβOs in older Tg mice attenuates synapse loss near plaques and abolishes loss further away [31].…”
Section: Therapeuticsmentioning
confidence: 96%
“…Another important factor in the present study was that anti-AβO Fabs could reduce various toxic Aβ species, including AβOs, toxic Aβ conformers, and N3pE Aβs. We previously demonstrated that anti-AβO antibodies lead AβOs to form nonfibrillar amorphous structures and play an important chaperone-like role in the Aβ aggregation pathway and allow Aβ to exist in a non-toxic state using a ThT assay and electron microscopy [ 21 ]. The present study verified the inhibitory effect on Aβ42 aggregation using a ThT assay and found that only 6H4 showed a long-lasting inhibitory effect on Aβ aggregation, such as primary nucleation and seeds (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of 6H4 on Aβ42 aggregation was evaluated using a ThT assay as described previously [ 13 , 21 ]. Briefly, Aβ42 (Merck, AG968) was monomerized with hexasuppleisopropanol and dissolved in 1% NH 4 OH.…”
Section: Methodsmentioning
confidence: 99%
“…Although a wide variety of organic compounds have been shown to inhibit Aβ 1–42 aggregation ( Fig 6 ) [ 10 15 ], many of them cannot be used because they are cytotoxic in cultured cells, favor the formation of oligomeric species, or have low bioavailability due to high molecular weights (>500 g/mol), which makes it difficult for them to cross lipid layers [ 42 ]. Because the cytotoxicity and genotoxicity of curcumin has been demonstrated in some cultured cells [ 47 ], several chemical analogs have been designed to overcome these limitations [ 12 ]. In addition, the activity of 1,2,3-hydroxyl- scyllo- inositol ( Fig 6 ) as a fibril-forming inhibitor has been demonstrated by ThT fluorescence and AFM [ 15 ].…”
Section: Discussionmentioning
confidence: 99%